Perlindungan Hukum bagi Korban Tindak Pidana Penipuan di Bidang Properti - Nanda Putri Mardi Utami (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The public's interest in the property sector has increased sharply along with the lure of the benefits that will be obtained. However, interest without being matched by extensive knowledge and experience in this field makes the community experience property crimes. The formulation of the problem in this study is first, what are the modes of property fraud perpetrators against their victims? Second, how is the legal protection for victims of property fraud? This research method uses normative legal research with a statutory and case approach and is processed in a qualitative descriptive manner. The results of the study conclude that: first, the modes of property fraud perpetrators against their first victims are a) Land mafia by targeting unconverted land, vacant land, and disputed land, b) The mode of fraud with the victim being a property agent, namely the fraudulent mode of the perpetrator by making fake certificates, c) The mode with the victim being the general public, namely the fraud mode in which the perpetrator offers or advertises property at a low price, but not in accordance with what was advertised or agreed upon, and d) A mode that uses the sharia label, so that many people are attracted to the lure of being free from usury and in the end the money is taken away. Second, legal protection for victims of property fraud is regulated through Article 378-395 Chapter XXV Book II of the Criminal Code and Articles 1 and 19 paragraphs (1) and (2) of Law Number 8 of 1999 concerning Consumer Protection.